Utilization of plasma as an ameliorator for forage productivity and in vitro traits of cowpea cultivated in salty soil - Hani S. Saudy; Mohamed F. Hamed; Taia A. Abd El-Mageed; Nasr E. El-Bordeny; Marwa A. Madkour; Mohamed H. Shokry; Gouda F. Gouda; Mariusz Jaremko; Abdul-Hamid Emwas; Abdelfattah T. Elgendy (Scientific Reports)
Abstract The adoption of advanced and practical technologies to boost plant productivity and improve quality under challenging environmental conditions, such as salinity, has become an essential need in modern agriculture. Plasma technology can significantly improve the seed’s resistance to stress factors like high salinity and dry environments. Thus, the current work aimed to improve the yield and quality of cowpea as an important forage crop grown in saline soil using a plasma coating approach. The seeds of cowpea were treated with three plasma doses expressed in different times of exposure (0.0, 1.0 and 2.0 min) and planted (for two seasons of 2022 and 2023) in three soil salinity levels expressed in electrical conductivity, EC (normal, 0.3 dS m−1, moderate salinity 5.5 dS m−1, and high salinity, 7.0 dS m−1, abbreviated as EC3.0, EC5.5 and EC7.0, respectively). The electron micrographs and elemental detection revealed that 2.0 min treatment resulted in deep cracking and topographical modulation with the best enhancements in cowpea seed surface nutrients. The agronomic findings revealed that compared to the corresponding check treatment (without plasma, 0.0 min), the exposure to plasma for 2.0 min in the first season was the efficient for enhancing forage yield under normal (1.37-fold increase) and medium salinity (1.79-fold increase). The in vitro data showed plasma-treated seeds for 2.0 min displayed higher acid detergent fiber content under EC3.0 or EC5.5 compared to the other treatments. Plants grown from seeds treated with plasma for 1.0 min showed higher dry matter degradability levels at EC7.0 compared to the other treatments. At EC7.0 the highest ammonia concentration was recorded in plants grown plasma-treated seeds for 1.0 min, while the lowest value was observed in 2.0-min. 2.0-min plasma-treated seeds produced the highest total volatile fatty acids across different salinity conditions, particularly at EC7.0. Plasma treatment, as a safe and innovative seed priming method, validates substantial potential in improving cowpea productivity under saline conditions. This study revealed that exposing cowpea seeds to a 2-min plasma treatment before sowing enhanced seed germination rate, and overall yield, even under challenging saline environments. Moreover, enhanced feed quality resulting from plasma-treated seeds offers direct benefits to livestock nutrition, supporting both human and animal food chains.